2018
DOI: 10.1596/1813-9450-8597
|View full text |Cite
|
Sign up to set email alerts
|

Remittances and Labor Supply in the Northern Triangle

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…A conflicting result was obtained by Posso (2012) wherein a study conducted across 66 developing nations indicated that external remittances resulted in an increase in aggregate labour supply in the remittance receiving region as migrant sending households stepped up labour supply to cover migration related expenses while demonstration effect caused non-migrant sending households to work more so as to facilitate migration by family members; besides remittances generated greater employment by overcoming credit constraints. Several other studies however find that remittances have a negative impact on labour supply by recipient households (Jadotte and Ramos 2015;Paul 2018;Sousa and Andres 2018). An interesting study by Rodriguez and Tiongson (2001) showed that in urban Philippines the labour supply reduction effects of remittances were more potent for males compared to females.…”
Section: Remittances and Labour Supply: A Review Of Literaturementioning
confidence: 98%
“…A conflicting result was obtained by Posso (2012) wherein a study conducted across 66 developing nations indicated that external remittances resulted in an increase in aggregate labour supply in the remittance receiving region as migrant sending households stepped up labour supply to cover migration related expenses while demonstration effect caused non-migrant sending households to work more so as to facilitate migration by family members; besides remittances generated greater employment by overcoming credit constraints. Several other studies however find that remittances have a negative impact on labour supply by recipient households (Jadotte and Ramos 2015;Paul 2018;Sousa and Andres 2018). An interesting study by Rodriguez and Tiongson (2001) showed that in urban Philippines the labour supply reduction effects of remittances were more potent for males compared to females.…”
Section: Remittances and Labour Supply: A Review Of Literaturementioning
confidence: 98%
“…He finds that remittances reduce child labour for girls and that this effect is only seen once an IV (2SLS) regression is ran. Sousa and Garcia-Suaza (2018) perform a propensity score matching to correct for the selection bias and find a small reduction in labour force participation among women. They also find that receiving remittances is associated with human capital development and leisure activities.…”
Section: Introductionmentioning
confidence: 99%
“…On the other side, remittances could increase investments in human capital or small businesses and self‐employment. Investments in human capital could result in higher skilled labour with higher wages that could overcome the increased reservation wage and especially in countries with imperfect credit market remittances can be used as alternative for credit and allow individuals to start self‐employed activities increasing labour supply (Sousa & Garcia‐Suaza, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations